Short Frenulum Prepuce - Goel, T. C.; Dubey, P. C.; Chandra, H. (Indian Journal of Plastic Surgery, 1986)
Twenty-seven patients of short frenulum, 15 acquired type and 12 congenital, are being presented. It produces difficulty in preputial retraction and dyspareunia. It can be effectively treated by frenuloplasty.